PANDANGAN MAHASISWA STKIP YAPIS DOMPU TERHADAP NILAI-NILAI MULTIKULTURALISME DALAM PROGRAM PERTUKARAN MAHASISWA MERDEKA - Ilyas Yasin; Retno Widya Ningrum; Sarifa Sarifa (Prodi PAI STIT Sunan Giri Bima, 2023)
Indonesia, with its complex level of pluralism, is always challenged to find new ways to instill citizens' awareness of the reality of the existing pluralism. Educational institutions are tasked with carrying out social engineering in creating a harmonious and peaceful society amidst the various differences that exist. Even though the number is small, the existence of non-Muslim minority students at STKIP Yapis Dompu still requires the cultivation of awareness and values of multiculturalism as the responsibility of the world of education. The participation of STKIP Yapis students in the Independent Student Exchange (PMM) activities in 2022 provides important experience in viewing the reality of pluralism both on campus and in society. The Nusantara module is one of the program materials that aims to provide participants with a multicultural perspective. In this module students are invited to visit various houses of worship, destinations and historical sites in the destination campus area. For students, this experience gives a different impression, especially for those who grew up in a homogeneous environment. PMM will also encourage campuses to formulate inclusive and protective policies to prevent the